(untitled) (Bulletin KNOB, 2025)
Since its introduction in 1912, the Auteurswet (Authors’ Act .copyright act) has protected works that have an ‘individual, original character’ and ‘bear the personal stamp of the maker’. The act grants that maker exclusive rights, including the right to exploitation. This means that the maker can decide for themselves how, where and when the work is made public or copied. In addition, the act confers personality rights, which protect the maker against changes or other impairments of the work that might damage their honour and reputation. Although the Auteurswet did not have its origins in the building industry, the act has certainly demonstrated its relevance to that sector, given that architects’ designs also fall under the protection of the act. Since 1912 several authors’ rights lawsuits have been filed in the context of the construction industry. These have focused in particular on the question of whether alterations to buildings encroach on the rights of the architect. Nowadays the debate often revolves around the tension between the creative vision of the architect on the one hand and functional or social interests on the other, such as a change of purpose. This leads to a weighing of interests in which the key consideration is how these interests relate to the personality rights of the architect. This article focuses on conflicts arising from changes to existing buildings during their architects’ lifetime. Four case histories are considered: the De Maerle villa (1917‑1918) in Huizen, the Metropool multi‑tenancy building (1991‑1992) in Amsterdam, the Ministry of Agriculture, Trade and Industry (2015) in The Hague, and the Naturalis Natural History Museum (2017) in Leiden. The key question is whether the arguments used in the evaluation and outcome of these cases have changed over time. The analysis of the four cases reveals that legislation, including the Auteurswet, is constantly subject to interpretation. In summary, the cases demonstrate that the act continues to evolve, partly in response to social change. There remains the important question of whether the application of the act (in other words, the interpretation of the weighing of interests) to architects’ designs is still consistent with current practice. The societal importance of preserving existing buildings and retrofitting them for sustainability is increasing. Demolition has become less acceptable from the viewpoint of sustainability, which only serves to heighten the tension between architectural authors’ rights and societal interests. Yet the jurisprudence shows that there is still scope for these societal interests. In the weighing of interests, arguments in favour of preserving a design are set against reasons for change, such as changing uses, modern functional requirements and sustainability. The cases discussed here illustrate how the interpretation of the Auteurswet has evolved and adapted to social change. This includes a greater focus on the personality rights of the maker. Although that does not result in a complete interdiction on changes to buildings, it does help to clarify the scope of these rights. It ensures that the Auteurswet remains balanced between creative freedom on the one hand and societal interests on the other, with room for continued development in the future.